2018
DOI: 10.4163/jnh.2018.51.4.295
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of health habit and hair mineral nutrition status of media addicted adolescent

Abstract: Purpose: Koreans' internet and smartphone usage hours are steadily increasing and the dependence of young people on smartphones is causing social problems. Therefore, this study was conducted to examine health and dietary habits, as well as hair mineral contents according to the level of dependence of smartphone use among adolescents to clarify the interrelation of smartphone dependence, lifestyle, dietary behavior, and mineral nutrition status. Methods: A total of 80 smartphone-addicted adolescents participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…5,9,10 According to a South Korean study that surveyed smartphone dependency and health habits, exposure to harmful social media was associated with smoking, drinking, and the consumption of unhealthy food. 11,12 Use duration and use for the purpose of communication are closely related to problematic smartphone use 13 and health problems. A previous study reported that high-frequency users tended to be more sedentary than low-frequency users.…”
Section: Introductionmentioning
confidence: 99%
“…5,9,10 According to a South Korean study that surveyed smartphone dependency and health habits, exposure to harmful social media was associated with smoking, drinking, and the consumption of unhealthy food. 11,12 Use duration and use for the purpose of communication are closely related to problematic smartphone use 13 and health problems. A previous study reported that high-frequency users tended to be more sedentary than low-frequency users.…”
Section: Introductionmentioning
confidence: 99%
“…In order to prolong the time spent in front of the screen, behavioral changes occur such as turning to easily prepared, high-calorie foods or skipping meals with snacks. 24,39 This situation increases the amount of calories taken and decreases the amount consumed, which paves the way for weight gain and obesity. In addition, the decrease in eating awareness related to distraction is one of the reasons for the inability to regulate eating in individuals with smartphone addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Spending a long time with a smartphone leads to a relatively sedentary life. In order to prolong the time spent in front of the screen, behavioral changes occur such as turning to easily prepared, high-calorie foods or skipping meals with snacks [ 24 , 38 ]. This situation increases the amount of calories taken and decreases the amount consumed, which paves the way for weight gain and obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to Internet use, smartphones are now a . In addition, overdependence has been reported to negatively affect not only family relationships, mental health, and sleep disturbances but also physical health and eating habits 4,5) . Furthermore, smartphone use is associated with decreased physical activity and has been reported to affect obesity rates depending on smartphone usage time 6,7)…”
Section: Introductionmentioning
confidence: 99%